Coordination environment dependent selectivity of single-site-Cu enriched crystalline porous catalysts in CO2 reduction to CH4 - Zhang, Yu; Dong, Long-Zhang; Li, Shan; Huang, Xin; Chang, Jia-Nan; Wang, Jian-Hui; Zhou, Jie; Li, Shun-Li; Lan, Ya-Qian (Nature communications, 2021)
The electrochemical CO 2 reduction to high-value-added chemicals is one of the most promising and challenging research in the energy conversion field. An efficient ECR catalyst based on a Cu-based conductive metal-organic framework (Cu-DBC) is dedicated to producing CH 4 with superior activity and selectivity, showing a Faradaic efficiency of CH 4 as high as ~80% and a large current density of −203 mA cm −2 at −0.9 V vs. RHE. The further investigation based on theoretical calculations and experimental results indicates the Cu-DBC with oxygen-coordinated Cu sites exhibits higher selectivity and activity over the other two crystalline ECR catalysts with nitrogen-coordinated Cu sites due to the lower energy barriers of Cu-O 4 sites during ECR process. This work unravels the strong dependence of ECR selectivity on the Cu site coordination environment in crystalline porous catalysts, and provides a platform for constructing highly selective ECR catalysts. Crystalline porous catalysts with single Cu sites are dedicated to exploring the dependence of CO 2 electroreduction selectivity on the coordination environment of catalytic sites. The conductive MOF Cu-DBC with oxygen-coordinated Cu sites shows a high Faradaic efficiency ~80% of CO 2 -to-CH 4 .